2019
DOI: 10.3758/s13421-018-0887-4
|View full text |Cite
|
Sign up to set email alerts
|

Are mnemonic failures and benefits two sides of the same coin?: Investigating the real-world consequences of individual differences in memory integration

Abstract: Theories of reconstructive memory have long been influenced by investigations of false recognition errors, in which old/new judgements are compromised by spontaneous activation of associated but nonpresented concepts. Recent evidence similarly suggests that reconstructive memory processes (so-called memory integration) also support positive learning behaviors, such as inferential reasoning. Despite prevailing hypotheses, the question of whether a common integration process underlies these seemingly disparate m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…Our study contributes to this literature by demonstrating that generalization across concepts in a novel semantic domain is better in the morning than evening. Specifically, we found that participants tested in the morning were not only better able to generalize a property (whether a satellite was "functional") to novel exemplars, but they also exhibited more generalization-related false memories, consistent with findings that generalization occurs alongside false memory formation Carpenter & Schacter, 2017;Varga et al, 2019, cf. de Araujo Sanchez & Zeithamova, 2020.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our study contributes to this literature by demonstrating that generalization across concepts in a novel semantic domain is better in the morning than evening. Specifically, we found that participants tested in the morning were not only better able to generalize a property (whether a satellite was "functional") to novel exemplars, but they also exhibited more generalization-related false memories, consistent with findings that generalization occurs alongside false memory formation Carpenter & Schacter, 2017;Varga et al, 2019, cf. de Araujo Sanchez & Zeithamova, 2020.…”
Section: Discussionsupporting
confidence: 83%
“…We assessed how encountering examples of satellites that combine features across previously separate categories facilitates the ability to generalize to novel satellites combining features from the same categories. Given that generalization can coincide with false memory formation Carpenter & Schacter, 2017;Varga et al, 2019, cf. de Araujo Sanchez & Zeithamova, 2020, we also examined false memories for these novel bridge satellites.…”
Section: Introductionmentioning
confidence: 99%
“…Adults' generalization relied on remembering specific item-context representations, consistent with the notion that rapid generalization relies on retrieving specific instances 7,8 and that there was no generalization-specificity trade-off. 28,29 These results suggest that adults' ability to rapidly generalize do not rely on abstractiona process by which memories for the specific instances are lost, but the emergent average representation supports generalization across episodes. 30 Instead, it relies on their ability to remember specifics and then integrate overlapping elements across episodes.…”
Section: What Determines Generalization?mentioning
confidence: 87%
“…As the last question, we were interested whether the degree of response bias is related to source memory. We especially aimed to test the hypothesis that false memory for inferred relationships may be a flip side of memory integration, whether it happens at encoding or in response to testdemands 9,23,24,32 . First, we compared false memory rates in participants who showed a negative response bias, no bias or a positive response bias (Figure 6A).…”
Section: False Memory and Response Biasmentioning
confidence: 99%